Quality of Pedestrian Networks Around Metro Stations: An Assessment Based on Approach Routes - Qiyao Yang; Zheng Zhang; Jun Cai; Mengzhen Ding; Lemei Li; Shaohua Zhang; Zhenang Song; Feiyang Chen; Yi Ling (Systems)
Walking is the primary mode of reaching metro stations, yet the quality of pedestrian networks around these stations has not been well researched. Considering the objective physical characteristics of pedestrian networks and the subjective assessments of walkers on the routes, this study developed an evaluation model that integrated the Analytic Hierarchy Process and Entropy Weight Method with human–machine adversarial scoring and cosine similarity to validate the reliability. Nineteen indicators concerning four fundamental criteria, including accessibility, convenience, safety, and comfort, were applied with data acquired from eight stations in Tianjin, China. Results reveal that accessibility and safety indicators weigh more than convenience and comfort indicators. The quality of pedestrian networks around the public-service and comprehensive stations scores higher than that around residential stations, while walking environment quality near commercial stations shows significant disparities. These findings highlight the importance of prioritizing accessibility and safety while enhancing convenience and comfort in the renewal of the pedestrian network in Tianjin. The assessment model provides a valuable tool for urban policymakers and planners, enabling the formulation of sound pedestrian-network policies, facilitating higher-quality walking access and egress trips to stations, and encouraging transit-oriented development.